Purifikasi Gas Metana (CH4) dari TPA Sampah Menggunakan Metode Water Scrubber - Sahwan, Firman Laili; Wahyono, Sri; Suryanto, Feddy; Hanif, Muhammad (Center for Environmental Technology - Agency for Assessment and Application of Technology, 2019)
ABSTRACTHigh population growth rate has stimulated the increase of energy consumption. Therefore, the use of renewable energy sources such as methane gas from landfill has also been encouraged. It is necessary that landfill methane gas is purified to increase its concentration. Common method to purify methane gas is water scrubber method. The aim of this research was to evaluate the effectiveness of landfill methane gas purification using a spray water scrubber (water scrubber method), a water column scrubber (bubbling methods) and the combination of both methods to increase the content of landfill methane. The experiment was conducted in the dry season and rainy season. Results of the study concluded that water scrubber was the most effective method for increasing methane gas concentration. The average increase of methane gas in the dry season were 33.32% (water scrubber) and 23.79% (combination of bubbling and water scrubber), and in the rainy season 8.89% (water bubbling) and 2.75% (combination of water scrubber and water bubbling). The increase in methane gas was due to a decrease in CO2Ã‚Â gas. In addition, there was an increase of H2O content in biogas from landfill after the purification process.Keywords: Landfill, methane gas, purification, water scrubberABSTRAKTingginya laju pertumbuhan penduduk telah memacu konsumsi energi yang terus meningkat. Oleh karena itu diperlukan upaya pemanfaatan sumber energi terbarukan, yang salah satunya adalah gas metana yang berasal dari TPA sampah. Keinginan untuk meningkatkan kandungan gas metana TPAÃ‚Â diperlukan upaya purifikasi, menggunakan metode water scrubber. Penelitian ini dilakukan dengan tujuan mengetahui efektivitas purifikasi gas metana TPA dengan menggunakan metode pengaliran gas dalam percikan air (water scrubber) dan metode pengaliran gas dalam air atau water bubblingÃ‚Â (serta kombinasi keduanya) untuk meningkatkan kandungan gas metana TPA, yang dilakukan pada musim kemarau dan musim penghujan. Hasil penelitian menyimpulkan bahwa water scrubberÃ‚Â merupakan metoda yang paling efektif untuk meningkatkan kandungan gas metana. Rata-rata peningkatan gas metana pada musim kemarau dan musim penghujan, berturut-turut sebesar 33,32% (water scrubber), 23,79 (kombinasi water bubblingÃ‚Â dan water scrubber), 8,89% (water bubbling) dan 2,75% (kombinasi water scrubberÃ‚Â dan water bubbling).Ã‚Â Peningkatan gas metana tersebut terjadi karena adanya penurunan gas CO2. Selain itu, terjadi peningkatan kandungan H2O pada biogas dari TPA setelah proses purifikasi.Kata kunci:Ã‚Â TPA, gas metana, purifikasi, water scrubber.